Earthquake-Related Orthopedic Injuries in Adult Population: A Systematic Review - Bortolin, Michelangelo; Morelli, Ilaria; Voskanyan, Amalia; Joyce, Nina R.; Ciottone, Gregory R. (Prehospital and disaster medicine, 2017)
Introduction Earthquake-related trauma results in crush injuries and bony- and soft-tissue trauma. There are no systematic reviews analyzing the typical injury patterns and treatments in "Mega-Mass-Casualty" earthquakes. The characterization of an injury pattern specific to disaster type, be it natural or manmade, is imperative to build an effective disaster preparedness and response system. The systematic review was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A comprehensive search strategy was developed to identify all publications relating to earthquakes and the orthopedic treatment in adult patients. The following databases were searched: PubMed (Medline; US National Library of Medicine, National Institutes of Health; Bethesda, Maryland USA), Ovid (Ovid Technologies; New York, New York USA), Web of Science (Thomson Reuters; New York, New York USA), and The Cochrane Library (The Cochrane Collaboration; Oxford, United Kingdom). The searches identified 4,704 articles: 4,445 after duplicates were removed. The papers were screened for title and abstract and 65 out of those were selected for full-text analysis. The quality of data does not permit a standard-of-care (SOC) to be defined. Scarcity and poor quality of the data collected also may suggest a low level of accountability of the activity of the international hospital teams. Qualitatively, it is possible to define that there are more open fractures during daytime hours than at night. Excluding data about open and closed fractures, for all types of injuries, the results underline that the higher the impact of the earthquake, as measured by Richter Magnitude Scale (RMS), the higher is the number of injuries. Discussion Regarding orthopedic injuries during earthquakes, special attention must be paid to the management of the lower limbs most frequently injured. Spinal cord involvement following spine fractures is an important issue: this underlines how a neurosurgeon on a disaster team could be an important asset during the response. Conservative treatment for fractures, when possible, should be encouraged in a disaster setting. Regarding amputation, it is important to underline how the response and the quality of health care delivered is different from one team to another. This study shows how important it is to improve, and to require, the accountability of international disaster teams in terms of type and quality of health care delivered, and to standardize the data collection. Bortolin M , Morelli I , Voskanyan A , Joyce NR , Ciottone GR . Earthquake-related orthopedic injuries in adult population: a systematic review. Prehosp Disaster Med. 2017;32(2):201-208.